Portuguese Artisanal Fishers’ Knowledge About Elasmobranchs—A Case Study - Silva, Priscila M.; Teixeira, Célia M.; Pita, Cristina; Cabral, Henrique N.; França, Susana (Frontiers in Marine Science, 2021)
The high economic value of fisheries was historically associated to commercial teleost fishes. Since the 1970s, despite some elasmobranchs becoming an important target or a bycatch, relatively little research has been carried out on this group because of their low economic value. Due to their specific life history characteristics, sharks and rays are particularly vulnerable to overexploitation, taking several decades to recover after reaching an overexploitation status. In Portugal elasmobranch fishery results mainly from targeted longlining and bycatch from different fishing gears. During the last decade, the Total Allowable Catches (TACs) of rays have been decreasing, the European Union (EU) banned the capture of some ray species, the Portuguese government implemented both a closed season and a minimum landing size for some rays, and the EU prohibited target fishing for sharks. All these measures may have been highly responsible for the national and local landings reduction. Official landings from the last decade were analyzed, the landed species conservation status was consulted, and structured interviews using a questionnaire were conducted in the most important fishing port in the Portuguese mainland, the port of Sesimbra. Results led us to conclude that fishers’ answers and landings data did not match. It also revealed a lack of awareness by fishers about the state of shark and ray populations, and about some aspects of their biology and ecology, like reproduction season and method. The present study highlights the need to fill in this existing gap in knowledge through the transfer of scientific knowledge and sharing of management responsibilities. Also, we aimed to demonstrate the necessity for awareness and education activities within fishing communities, an essential step to elasmobranch conservation.